Characterisation of Zamorano-Leonese Donkey Milk as an Alternative Sustainably Produced Protein Food - Albertos, Irene; López, María; Jiménez, José-María; Cao, María José; Corell, Alfredo; Castro-Alija, María José (Frontiers in Nutrition, 2022)
The Zamorano-Leonese donkey is the local breed of the Castilla y León region of Spain and is a protected endangered species. The best way to preserve it is to explore viable alternatives such as milk production. Unlike other donkey breeds, this one has not been previously characterised. The aim of this work is the complete nutritional characterisation of its milk for human consumption, either directly or as an ingredient, to meet the new consumer expectations of sustainability and health concerns. This breed did not differ from others in terms of amino acid and protein profile. Its low concentration of β-lactoglobulin may be correlated to a low allergenicity. The presence of lactozyme and lactoferrin, which are potent antimicrobials, stand out among the proteins. This milk presented a higher content of unsaturated fatty acids, being oleic fatty acid the main one. Zamorano-Leonese donkey milk did have a higher content of vitamin C, riboflavin, folic acid and vitamin E than the other donkey breeds. It also had a high concentration of vitamin D despite its low-fat content. However, its mineral concentration was lower than other donkey breeds in line with its lower ash content. In terms of micronutrients, it had a high amount of zinc and selenium. Based on these results we can conclude that donkey milk is a food and/or ingredient with beneficial effects on cardiovascular health and the proper functioning of the immune system, as well as being a good source of protein. Therefore, donkey milk from this local species from Spain is a food and/or ingredient with beneficial nutritional properties and sustainable from an environmental point of view.